Jasmonate-responsive expression of paclitaxel biosynthesis genes in Taxus cuspidata cultured cells is negatively regulated by the bHLH transcription factors TcJAMYC1, TcJAMYC2, and TcJAMYC4 - Lenka, Sangram K.; Nims, N. Ezekiel; Vongpaseuth, Kham; Boshar, Rosemary A.; Roberts, Susan C.; Walker, Elsbeth L. (Frontiers in Plant Science, 2015)
Taxus cell suspension culture is a sustainable technology for the industrial production of paclitaxel (Taxol®), a highly modified diterpene anti-cancer agent. The methyl jasmonate (MJ)-mediated paclitaxel biosynthetic pathway is not fully characterized, making metabolic engineering efforts difficult. Here, promoters of seven genes (TASY, T5αH, DBAT, DBBT, PAM, BAPT and DBTNBT), encoding enzymes of the paclitaxel biosynthetic pathway were isolated and used to drive MJ-inducible expression of a GUS reporter construct in transiently transformed Taxus cells, showing that elicitation of paclitaxel production by MJ is regulated at least in part at the level of transcription. The paclitaxel biosynthetic pathway promoters contained a large number of E-box sites (CANNTG), similar to the binding sites for the key MJ-inducible transcription factor AtMYC2 from Arabidopsis thaliana. Three MJ-inducible MYC transcription factors similar to AtMYC2 (TcJAMYC1, TcJAMYC2 and TcJAMYC4) were identified in Taxus. Transcriptional regulation of paclitaxel biosynthetic pathway promoters by transient over expression of TcJAMYC transcription factors indicated a negative rather than positive regulatory role of TcJAMYCs on paclitaxel biosynthetic gene expression.